Degradation of acrylamide by the UV/chlorine advanced oxidation process. (November 2017) - Gao, Ze-Chen; Lin, Yi-Li; Xu, Bin; Pan, Yang; Xia, Sheng-Ji; Gao, Nai-Yun; Zhang, Tian-Yang; Chen, Ming
Abstract: The degradation of acrylamide (AA) during UV/chlorine advanced oxidation process (AOP) was investigated in this study. The degradation of AA was negligible during UV irradiation alone. However, AA could be effectively degraded and mineralized during UV/chlorination due to the generation of hydroxyl radicals (OH). The degradation kinetics of AA during UV/chlorination fitted the pseudo-first order kinetics with the rate constant between AA and OH radicals being determined as 2.11 × 10 9 M −1 s −1 . The degradation rate and mineralization of AA during UV/chlorination were significantly promoted at acidic conditions as well as increasing chlorine dosage. The volatile degradation products of AA during UV/chlorination were identified using gas chromatography-mass spectrometry and the degradation pathways were then proposed accordingly. The formation of disinfection by-products (DBPs) in Milli-Q water and tap water during UV/chlorination of AA was also investigated. The DBPs included chloroform, dichloroacetonitrile, trichloroacetonitrile, 2, 2-dichloroacetamide and 2, 2, 2-trichloroacetamide. Furthermore, the variations of AA degradation during UV/chlorination in different real water samples were evaluated. Graphical abstract: Highlights: UV/chlorine advanced oxidation process (AOP) degraded acrylamide more efficiently than UV irradiation or chlorination alone. Weakened formation of the total DBPs in tap water compared with that in Milli-Q water during UV/chlorination were detected. The formation pathways of volatile degradation products during UV/chlorination of acrylamide were proposed. UV/chlorine process was feasible in practical application to control acrylamide concentration in drinking water.